Efficacy of gabapentin in the improvement of pruritus and quality of life of patients with notalgia paresthetica - Ana Alice Wolf Maciel; Paulo Rowilson Cunha; Isabela Ortiz Laraia; Flávia Trevisan (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: notalgia paresthetica is a subdiagnosed sensory neuropathy presenting as a condition of intense itching and hyperchromic macule on the back that interferes with daily habits. OBJECTIVES: To determine the efficacy of treatment of notalgia paresthetica using oral gabapentin, assessing the degree of improvement in itching and influence on quality of life. Moreover, to evaluate the signs and symptoms associated with notalgia paresthetica. METHODS: We conducted an experimental, non-randomized, parallel, non-blinded study including 20 patients with clinical and histopathological diagnosis of notalgia paresthetica. After application of the visual analogue scale of pain adapted for pruritus and of the questionnaire of dermatology life quality index (DLQI), ten patients with visual analogue scale > 5 were given treatment with gabapentin at the dose of 300 mg/day for four weeks. The other ten were treated with topical capsaicin 0.025% daily for four weeks. After the treatment period, patients answered again the scale of itching. RESULTS: The use of gabapentin was responsible for a significant improvement in pruritus (p=0.0020). Besides itching and hyperchromic stain on the back, patients reported paresthesia and back pain. It was observed that the main factor in the worsening of the rash is heat. CONCLUSION: Gabapentin is a good option for the treatment of severe itching caused by nostalgia paresthetica.